PSYCHOMETRIC PROPERTIES OF A TURKISH VERSION OF THE COMPULSIVE INTERNET USE SCALE - Kuzucu, Yasar; Ozdemir, Yalcın; Ak, Serife (European Scientific Journal, ESJ, 2015)
This study aimed to examine the psychometric properties of the Compulsive Internet Use Scale (CIUS) in a Turkish adolescent sample. The data were collected from 409 adolescents. The sample included 229 (56%) females and 180 (44%) males. The age of the participants ranged between 16 and 18 years with a mean age of 17.3 (SD= 1.3). Adolescent ages 16- 18).First, the factor structure of the scale was examined and the results of the explanatory and confirmatory factor analyses showed that the CIUS is a onedimensional construct.As for the convergent validity; the correlations of CIUS with measures of Internet addiction were examined. For divergent validity; the correlations of CIUS with measures of social and emotional loneliness and depression were examined. These results revealed strong correlations. Following, reliability wasexamined via internal consistency, test-re-test reliability coefficients and split-half correlation. Reliability analyses showed that the scale had high internal consistency, high test-retest and split half reliabilities. The results of the present study indicate that Turkish version of CIUS has good psychometric properties.Finally, findings were discussed in line with the relevant literature.